2015
DOI: 10.1002/eji.201444874
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimer‐specific TLR2 stimulation results in divergent functional outcomes in B‐cell precursor acute lymphoblastic leukemia

Abstract: Reports of spontaneous acute lymphoblastic leukemia (ALL) remissions following severe bacterial infections suggest that bacterial components may trigger elimination of ALL. To date, TLR2, which recognizes a broad range of bacterial pathogens through TLR1 or TLR6 heterodimerization, has not been fully evaluated for direct effects on ALL. Studies investigating TLR2 signaling in other tumor cell types utilizing single ligands have yielded contradictory results, and comparative, heterodimer-specific analyses of TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…It was shown that administration of TLR2 agonists can enhance effector and memory T cell responses, culminating in improved tumor rejection [ 270 , 271 ]. TLR2 agonists can also increase expression of costimulatory molecules in B cell lymphoma, enhancing its sensitivity to NK and CD8 + T cells [ 272 ], or inducing caspase 8-dependent apoptosis [ 273 ].…”
Section: Type I Interferons In Cancer Therapymentioning
confidence: 99%
“…It was shown that administration of TLR2 agonists can enhance effector and memory T cell responses, culminating in improved tumor rejection [ 270 , 271 ]. TLR2 agonists can also increase expression of costimulatory molecules in B cell lymphoma, enhancing its sensitivity to NK and CD8 + T cells [ 272 ], or inducing caspase 8-dependent apoptosis [ 273 ].…”
Section: Type I Interferons In Cancer Therapymentioning
confidence: 99%
“…The finding of an enrichment of cell death pathway signatures already 3 hours after Pam3CSK4 treatment of MA9 cells suggests that induction of an apoptosisassociated transcriptional program is an early consequence of TLR1/TLR2 activation. Agonistic targeting of TLR1/TLR2 has previously been shown to sensitize acute lymphoblastic leukemia cells for vincristine-mediated cytotoxicity, 47 to enhance the cytotoxic and apoptotic effects of bortezomib in myeloma cells, and to induce cell death of monocytes from tuberculosis patients, 48,49 but induction of apoptosis after TLR1/TLR2 activation has not previously been described in the context of AML. The observed differentiation of AML cells is consistent with a described cellular response to TLR1/TLR2 activation in normal myeloid progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[66,67] In addition, the GMP subtype was characterised by enhanced innate immune activity, especially through Toll-like receptor (TLR) signaling, which was impaired in the MEP subtype. Enhanced expression of TLRs has been associated with haematopoietic malignancies, [68][69][70][71] including AML, [68,72,73] but their role in pathogenesis remains unclear. Nevertheless, enhanced TLR signaling could activate inflammatory cytokine secretion and downstream effectors, which might explain the observed upregulation of IL-6 JAK-STAT3 signaling and coregulation of TNF-α signaling through NF-κB and IFN-γ signaling in the GMP subtype.…”
Section: Plos Onementioning
confidence: 99%